Construction of Synergistic Ni3S2‐MoS2 Nanoheterojunctions on Ni Foam as Bifunctional Electrocatalyst for Hydrogen Evolution Integrated with Biomass Valorization. Issue 24 (16th May 2022) - Yang, Shaowei; Guo, Ying; Zhao, Yike; Zhang, Ling; Shen, Haidong; Wang, Jinhui; Li, Jinjin; Wu, Chen; Wang, Wenbin; Cao, Yueling; Zhuo, Sifei; Zhang, Qiuyu; et al.
Abstract: The intrinsic sluggish kinetics of the oxygen evolution reaction (OER) limit the improvement of hydrogen evolution reaction (HER) performance, and substituting the anodic oxidation of biomass materials is an alternative approach, given its lower oxidation potential and higher added value compared to those of OER. In this study, a Ni3 S2 ‐MoS2 nanoheterojunction catalyst with strong electronic interactions is prepared. It exhibits high efficiency for both the HER and the electrooxidation of 5‐hydroxymethylfurfural (HMF). In a two‐electrode cell with Ni3 S2 ‐MoS2 serving as both the anode and cathode, the potential is only 1.44 V at a current density of 10 mA cm −2, which is much lower than that of pure water splitting. Density functional theory calculations confirm that the strong chemisorption of H and HMF at the interface leads to outstanding electrocatalytic activity. The findings not only provide a strategy for developing efficient electrocatalysts, but also provide an approach for the continuous production of high value‐added products and H2 . Abstract : The utilization of solar energy is an effective way to solve the energy crisis. Employing solar cells to drive the coupling reaction of electrocatalytic biomass oxidation and hydrogen evolution can perfectly convert solar energy into chemical energy and hydrogen energy. Therefore, it is of great significance to develop efficient bifunctional electrode materials to achieve the goal.